2014
DOI: 10.3390/ijerph110909491
|View full text |Cite
|
Sign up to set email alerts
|

Increased NQO1 but Not c-MET and Survivin Expression in Non-Small Cell Lung Carcinoma with KRAS Mutations

Abstract: Cigarette smoking is one of the most significant public health issues and the most common environmental cause of preventable cancer deaths worldwide. EGFR (Epidermal Growth Factor Receptor)-targeted therapy has been used in the treatment of LC (lung cancer), mainly caused by the carcinogens in cigarette smoke, with variable success. Presence of mutations in the KRAS (Kirsten rat sarcoma viral oncogene homolog) driver oncogene may confer worse prognosis and resistance to treatment for reasons not fully understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…In previous studies our laboratory, as well as other investigators, reported that NQO1 expression levels were highly elevated in lung cancer patient tumor versus associated normal lung tissue (9, 24). Elevated tumor-NQO1 levels have provided a distinct advantage for developing NQO1-directed anticancer therapeutics such as β-lapachone and deoxyniboquinone (13, 14).…”
Section: Resultsmentioning
confidence: 70%
“…In previous studies our laboratory, as well as other investigators, reported that NQO1 expression levels were highly elevated in lung cancer patient tumor versus associated normal lung tissue (9, 24). Elevated tumor-NQO1 levels have provided a distinct advantage for developing NQO1-directed anticancer therapeutics such as β-lapachone and deoxyniboquinone (13, 14).…”
Section: Resultsmentioning
confidence: 70%
“…Second, inhibition of SCD would reduce the synthesis of only desaturated FAs but not saturated ones (25,34). Third, FASN inhibition would be specific to the FA synthesis pathway, which would deplete both desaturated and saturated FA production (35,36). Cerulenin is an inhibitor of FASN (36,37) (Fig.…”
Section: Kras-associated Induction Of Fasn Is Required For Lung Cancementioning
confidence: 99%
“…Such finding has led to the suggestion that NQO1 can be important in cancer chemoprevention. However, polymorphism in the NQO1 gene has been reported to be associated with an increased risk of various cancers such as breast [ 10 ], lung [ 11 ], gastric [ 24 ] and head and neck cancer [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…NQO1 has positive cytoplasmic expression in 76%, 60% and 65% in cervical, endometrial and ovarian carcinoma respectively. Previous studies demonstrated that NQO1 immunopositivity rate ranged between 21% and 80% [ 10 , 11 , 28 ] in various tumors. We found increased NQO1 expression from normal tissue to SIL and cervical carcinoma and then from SIL to carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation